Modeling performance of railways nodes as intermodal terminals - Vasiliauskas, Aidas V. (Transport, 2006)
Present performance of railway transport sector is determined by two groups of factors. The first one relates to the changes of external economic environment of railway performance, while the second one deals with the internal changes in the railway transport sector. These factors determine priority directions of railway transport sector development. A good example of such development is implementation of intermodal services, which in turn foresee concept of integration of various logistics service providers. In this paper assumption is made, that implementation of intermodal services as well as integration of various logistics services providers can not be reached without proper nodes on the multimodal transport networks. Therefore definition, urge and some key functions of intermodal terminal are discussed. Later theoretical model of such terminal performance is presented. The paper ends with conclusions about the meaning of intermodal terminal to the increase of quality level of railway transport sector performance. First Published Online: 27 Oct 2010